2015
DOI: 10.3855/jidc.5868
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and phenotypic characteristics of methicillin-resistant Staphylococcus aureus isolated from hospitalized patients

Abstract: Introduction: Methicillin-resistant Staphylococcus aureus (MRSA) is one of the leading causes of infections acquired in both community and hospital settings. In this study, MRSA isolated from different sources of hospitalized patients was characterized by molecular and phenotypic methods. Methodology: A total of 123 S. aureus isolates were characterized according to their genetic relatedness by repetitive element sequence based-PCR (REP-PCR), in vitro antimicrobial susceptibility profile, SCCmec typing and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
17
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 45 publications
3
17
2
1
Order By: Relevance
“…The predominance of SCCmec type II (34/52, 65.4%) was also observed among the MRSA strains isolated from patients with bloodstream and respiratory tract infections during 2015-2016 in the University Hospital of Londrina in the Parana State, Brazil 20 . Interestingly, the predominance of MRSA strains harboring SCCmec II elements was also observed in a study during 2010 to 2013 in the same hospital 21 . These data suggest the shift in the MRSA population and emphasizes on the substitution of the strains harboring SCCmec III with those carrying SCCmec II that is becoming prevalent in some areas 19,20 .…”
Section: Discussionsupporting
confidence: 67%
“…The predominance of SCCmec type II (34/52, 65.4%) was also observed among the MRSA strains isolated from patients with bloodstream and respiratory tract infections during 2015-2016 in the University Hospital of Londrina in the Parana State, Brazil 20 . Interestingly, the predominance of MRSA strains harboring SCCmec II elements was also observed in a study during 2010 to 2013 in the same hospital 21 . These data suggest the shift in the MRSA population and emphasizes on the substitution of the strains harboring SCCmec III with those carrying SCCmec II that is becoming prevalent in some areas 19,20 .…”
Section: Discussionsupporting
confidence: 67%
“… 14 ; b PVL: Panton Valentine Leukocidin encoding gene and tst-1 : Toxic Shock Syndrome Toxin encoding gene were detected as described in Oliveira et al . 16 ; c Antimicrobial resistance profile was determined by disk-diffusion assay according to the CLSI guidelines 8 - I: OXA; II: OXA, ERI, CLI, CIP; III: OXA, ERI, CLI, CIP, GN; OXA: Oxacillin, CLI: Clindamycin, ERI: Erithromycin, CIP: Ciprofloxacin; GN: Gentamicin; d Year of isolation; e Source of isolation, T: Tracheal secretion, B: Blood; f MIC vancomycin determined by E-test ; - Absence; + Presence.…”
mentioning
confidence: 99%
“…Although the Brazilian endemic clone (BEC) with SCCmec type III has been shown to be the clone that is spread in Brazil, this was not the SCCmec type found most frequently in our isolates; indeed, SCCmec type II was most prevalent, according to another study described by Oliveira et al [43]. Furthermore, the analysis of DNA polymorphism performed in our study showed a low genetic similarity (45%) of strain BEC9393 with most of the strains studied.…”
Section: Discussionmentioning
confidence: 48%